Supply Chain Analysis and Distribution Of Chicken Meat (Case Study UD Naya Chicken Cut, East Binjai District) - Riza Ayu Asmita; Tasya Yustika Putri; Siti Aisyah (Journal of Indonesian Management, 2022)
This journal reviews how the supply chain and distribution occur at the UD Naya chicken stall in the East Binjai sub-district. This type of research uses a qualitative research approach that describes the results of research in the form of descriptive data. This type of research has a definition of the research subject, namely fresh chicken meat and how it is supplied. This study took the object of chicken meat that was sold at the UD Naya chicken stall. The research method used is the interview method to the resource persons and literature study. The results obtained from the interview method are that there are 3 supply chain processes that occur at the UD Naya chicken stall, namely: (1) Suppliers (chicken breeders) - Sales Agents - UD Naya Kiosk - Final Consumers. (2) Suppliers (chicken farmers) – Sales agents – UD Naya Kiosk – Small/mobile traders – Final consumers and (3) Suppliers (chicken farmers) – Sales agents – UD Naya Kiosk – Restaurants – Final Consumers.